A new numerical approach in the seismic failure analysis of concrete gravity dams using extended finite element method. (February 2022) - Haghani, Majid; Neya, Bahram Navayi; Ahmadi, Mohammad Taghi; Amiri, Javad Vaseghi
Highlights: A new approach has been developed to conduct seismic failure analysis of concrete gravity dams using extended finite element method. To perform the failure analysis dynamic stress intensity factors based on interaction integral with dynamic effects are utilized. The penalty method is used to model the opening and closing of cracks due to seismic loading. Numerical parameters such as assembling of mass matrix, using high-order elements and penalty parameter are discussed. Abstract: In this paper, a new approach has been developed to conduct seismic failure analysis of concrete gravity dams using extended finite element method and evaluated numerical parameters of dam-foundation-reservoir system. Failure analysis of concrete gravity dams are investigated using Extended finite element method (XFEM) combined with time integration by α-method. To perform the failure analysis and dynamic fracture behavior of a cracked dam, dynamic stress intensity factors based on interaction integral with dynamic effects are utilized. The penalty method is used in this study to model the opening and closing of cracks due to seismic loading. In addition, to apply the interaction between dam, foundation and reservoir in finite element model, zero thickness six-nodal contact elements are used in which the system formulated with lagrangian approach. To achieve this goal, several examples are first reviewed to validate the proper performance of a written code, and the results are then compared with those reported in the literature. Then, numerical parameters in seismic failure analysis such as length of crack growth, angle of initial crack, assembling of mass matrix, using high-order elements and penalty parameter discussed. The results show when cracks start to propagate, in the numerically approach, tip elements will switch to elements that fully cut by cracks. This transformation produces shockwaves during failure analysis. Obtained results show by using crack tip element, the analysis is numerically unstable and does not end. Using eight-node elements with four nodes enriched only by the Heaviside jump function and elimination of enrichment functions of the crack tip are reduced the failure analysis costs while good accuracy. In addition, a different crack path created when diagonal and consistent mass matrix used in the failure analysis.